The development and evaluation of a smoking cessation programme for disadvantaged pregnant women in South Africa - Everett-Murphy Katherine (Department of Public Health and Family Medicine, 2014)
Studies of smoking during pregnancy in South Africa have found exceptionally high smoking rates among disadvantaged women of mixed ethnic descent (46%) (Steyn et al., 1997; Petersen et al., 2009a). As a consequence, these women are at high risk of smoking-related pregnancy complications and poor birth outcomes. It has long been recommended that a smoking cessation intervention be developed specifically for this high risk group. There is strong evidence that best practice smoking cessation interventions for pregnant women can be effective in increasing quit rates, as well as in reducing the incidence of premature birth and low birth weight (Lumley et al., 2009). However, these interventions have only been studied in developed countries and it was unknown whether such programmes could be successfully applied to a South African setting. From 2002, the Medical Research Council of SA undertook a programme of research for the purposes of developing and evaluating a smoking cessation intervention, specifically for disadvantaged pregnant women attending public-sector, antenatal clinics in Cape Town. This thesis reports on several aspects of this research.